2001
DOI: 10.1021/ja003346i
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Charge Separation and Charge Recombination Dynamics in Porphyrin−Fullerene Linked Dyads and Triads:  Marcus-Normal versus Inverted Region

Abstract: Photoinduced charge separation (CS) and charge recombination (CR) processes have been examined in various porphyrin-fullerene linked systems (i.e., dyads and triads) by means of time-resolved transient absorption spectroscopy and fluorescence lifetime measurements. The investigated compounds comprise a homologous series of rigidly linked, linear donor-acceptor arrays with different donor-acceptor separations and diversified donor strength: freebase porphyrin-C60 dyad (H2P-C60), zincporphyrin-C60 dyad (ZnP-C60)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
398
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 546 publications
(425 citation statements)
references
References 128 publications
25
398
1
1
Order By: Relevance
“…2) in a linked triad, ZnP-H 2 P-C 60 (8,9), in which the zinc tetraphenylporphyrin (ZnP), free-base tetraphenylporphyrin (H 2 P), and fullerene (C 60 ) moieties (N-methyl-2-phenyl-3,4-fulleropyrrolidine) are rigidly linked by amide spacers (Fig. 1A).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2) in a linked triad, ZnP-H 2 P-C 60 (8,9), in which the zinc tetraphenylporphyrin (ZnP), free-base tetraphenylporphyrin (H 2 P), and fullerene (C 60 ) moieties (N-methyl-2-phenyl-3,4-fulleropyrrolidine) are rigidly linked by amide spacers (Fig. 1A).…”
mentioning
confidence: 99%
“…T o construct nanoscale devices or molecular wires that efficiently convert photon energies to chemical potentials, extensive studies have produced photoinduced, long-distance charge separation (CS) states by using donor (D)-acceptor (A)-linked multiarray systems that mimic natural photosynthesis (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). In each intramolecular, sequential electron transfer (ET) step, an electron or a hole tunnels between D and A over substantial distances (Ͼ10 Å) as in the natural photosynthetic reaction centers (12).…”
mentioning
confidence: 99%
“…Porphyrinogen formation is known to be often reversible. Hence, along with the independent formation of A 3 B-porphyrin and other porphyrins, the obtained B 4 -porphyrinogen reacts with aldehyde 8 b or 8 d leading to the whole set of A x B 4Àx porphyrins, but these reactions proceed at lower rates than the formation of B 4 . On the contrary, the Lewis basicities of 8 a and 8 c are close to that of 7 and therefore in these cases aldehydes of both types, A and B, are activated to similar extents.…”
Section: Synthesismentioning
confidence: 99%
“…Fullerene and its functionalized derivatives were soon preferred to quinones, because it was observed that they can considerably accelerate charge separation, while at the same time slowing down charge recombination [56,57].…”
Section: Supramolecular Assembliesmentioning
confidence: 99%